Job Insecurity and Work Engagement in Retail Employees at PT.X - Agustina, Vella Fitrisia (Jurnal Ar Ro'is Mandalika (Armada), 2026)
Work engagement As a behavior that can improve productivity and performance in companies, it needs to be studied amidst socioeconomic changes and technological developments that threaten employee job security. This study aims to examine the relationship between job insecurity and work engagement. Data collection to measure work engagement usedUtrecht Work Engagement Scale(UWES),To measure job insecurity, the Job Insecurity Scale (JIS) was used. A random sampling technique was used to select 150 subjects working in the retail sector. Data analysis using Spearman's Rank correlation showed a p-value of <0.05 and r-value of -0.162, indicating a relationship between job insecurity and work engagement among retail employees at PT. X.